Her Hands: Images of Craftswomen in Uganda, Bolivia and India - Shealy, Shaina (Consilience, 2011)
Throughout the world, women employ their craft skills to contribute to their economies and gain financial independence. This photo essay exhibits craftswomen in Bolivia, Uganda and India, and reflects on the economic and social benefits they reap as a consequence of the art they produce. The featured photos examine art production by women as a catalyst of economic development, women’s social and financial empowerment and independence, and positive social change within economically lesser-developed communities.